IMPLEMENTASI METODE ALBIDAYAH DALAM PEMBELAJARAN MEMBACA KITAB KUNING DI MADIN ALFALAH CERME LOR - kusdianto; Hasan Basri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
This research aims to determine the methods used in Nahwu Shorof learning and also the supporting and inhibiting factors in the Nahwu Shorof learning process at MADIN Alfalah in Cerme Lor Cerme Gresik Village. By carrying out this research, it is hoped that it can increase knowledge and provide benefits for those involved in the NahwuShorof learning process in general, especially for MADIN Alfalah itself as the location where this research was conducted. The research method used is qualitative descriptive research. Data collection uses observation, interviews and documentation methods. Data analysis is carried out by giving meaning to the data obtained and then drawing conclusions. The results of the research show that (1) The learning resource (book) used in learning nahwu shorof at MADIN Alfalah is the Albidayah Method Book. (2) The learning method for the science of nahwu shorof at MADIN Alfalah uses the Al-hifdhu, Al-fahmu, and Al-tathbiq methods. Apart from learning activities in class which are a supporting factor in the nahwu shorof learning process, the MADIN Alfalah teachers often hold competition activities in the art of reading and writing the Koran, reading the bald book, speeches, and so on. Meanwhile, inhibiting factors include students' varying levels of intelligence, as well as limited learning time.